Domestic Banks as Lightning Rods? Home Bias and Information during the Eurozone Crisis - Orkun Saka (Center for Economic Studies and ifo Institute (CESifo), 2019)
European banks have been criticized for holding excessive domestic government debt during the recent Eurozone crisis, which may have intensified the diabolic loop between sovereign and bank credit risks. By using a novel bank-level dataset covering the entire timeline of the Eurozone crisis, I first re-confirm that the crisis led to the reallocation of sovereign debt from foreign to domestic banks. In contrast to the recent literature focusing only on sovereign debt, I show that the banks' private sector exposures were (at least) equally affected by the rise in home bias. Consistent with this pattern, I propose a new debt reallocation channel based on informational frictions and show that the informationally closer foreign banks increase their relative exposures when the sovereign risk rises. The effect of informational closeness is economically meaningful and robust to the use of different information measures and controls for alternative channels of sovereign debt reallocation.
Keywords: F21; F34; F36; G01; G11; G21; 330; home bias; information asymmetries; Eurozone crisis; sovereign debt